Determinan Kecintaan Uang, Locus Of Control, Dan Income Terhadap Persepsi Etis dan Perilaku Keuangan Usaha Kecil Menengah Kota Makassar: Sebuah Telaah Religiusitas - Adya Utami Syukri; Jumria (Jurnal Online Manajemen ELPEI, 2023)
The reality that exists in today's society shows a consumptive lifestyle that is not in accordance with the income received, financial conditions and a lack of knowledge and perspectives on financial conditions which can eventually lead to financial failure. The financial behavior of the Indonesian people who tend to be consumptive then gives rise to various other irresponsible financial behaviors such as a lack of saving, investing, emergency fund planning and budgeting for the future. This study aims to look at the determinants between the love of money, locus of control, income on ethical perceptions and financial behavior of small and medium enterprises in the city of Makassar and also from a religious perspective. In order to achieve the research objectives and provide answers to the problems posed, this research uses quantitative methods by taking cross-sectional data in the form of responses from employees. These responses will be obtained through surveys both online and non-online using the purposive sampling method, namely the method of giving questionnaires to UKM members who are willing to respond when contacted or visited. The questionnaire proposed was compiled based on questions that have been commonly used in analyzing love of money, locus of control, income, gender and moderating religiosity on ethical perceptions and financial behavior of members. To see the relationship between the variables of this study using multiple linear regression analysis and descriptive analysis. The results showed that the income variable had a positive and significant effect and the religiosity variable had a negative and significant effect on ethical perceptions and financial behavior.